Cooperation between myofibril growth and costamere maturation in human cardiomyocytes - Shi, Huaiyu; Wang, Chenyan; Gao, Bruce Z.; Henderson, James H.; Ma, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
Costameres, as striated muscle-specific cell adhesions, anchor both M-lines and Z-lines of the sarcomeres to the extracellular matrix. Previous studies have demonstrated that costameres intimately participate in the initial assembly of myofibrils. However, how costamere maturation cooperates with myofibril growth is still underexplored. In this work, we analyzed zyxin (costameres), α-actinin (Z-lines) and myomesin (M-lines) to track the behaviors of costameres and myofibrils within cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CMs). We quantified the assembly and maturation of costameres associated with the process of myofibril growth within the hiPSC-CMs in a time-dependent manner. We found that asynchrony existed not only between the maturation of myofibrils and costameres, but also between the formation of Z-costameres and M-costameres that associated with different structural components of the sarcomeres. This study helps us gain more understanding of how costameres assemble and incorporate into the cardiomyocyte sarcomeres, which sheds a light on cardiomyocyte mechanobiology.